2020
DOI: 10.21101/cejph.a6345
|View full text |Cite
|
Sign up to set email alerts
|

Early childhood caries in multilingual community

Abstract: Objective: The aim of the study was to determine the prevalence and severity of early childhood caries (ECC) among different social groups of preschool children in ethnic and multilingual diverse community such as South Backa District (SBD), Republic of Serbia.Methods: This survey was a cross-sectional analytical study and sample type has been projected by simple random choice of 13-71 months old children together with their parents of varied socioeconomic status (SES) and nationality in SBD. Preschool childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…The higher prevalence of dental caries and untreated tooth decay in primary and permanent dentitions in immigrant children compared with Spanish children is consistent with previous studies both in Spain [23] and in Europe [9,11,15,31]. Studies conducted in Slovakia and Serbia [35,36] also show higher prevalence of tooth decay in Spanish Roma children. In addition, in the case of Spanish Roma children, it is important to point out that in primary teeth, the proportions of dental caries and untreated tooth decay experience were equal, which confirms the low use of preventive and restorative dental visits in this population [35].…”
Section: Discussionsupporting
confidence: 90%
“…The higher prevalence of dental caries and untreated tooth decay in primary and permanent dentitions in immigrant children compared with Spanish children is consistent with previous studies both in Spain [23] and in Europe [9,11,15,31]. Studies conducted in Slovakia and Serbia [35,36] also show higher prevalence of tooth decay in Spanish Roma children. In addition, in the case of Spanish Roma children, it is important to point out that in primary teeth, the proportions of dental caries and untreated tooth decay experience were equal, which confirms the low use of preventive and restorative dental visits in this population [35].…”
Section: Discussionsupporting
confidence: 90%
“…Saddki et al (2010) in this regard, consider that more frequent visits to dentists are associated with better educational status and prenatal regular visits. Obstacles to seeking dental services also include poor perception of the quality of care provided, language barriers (Tušek et al, 2020) as well as the husband's influence on the pregnant woman's decision to see a dentist. There are barriers by dentists as well.…”
Section: Resultsmentioning
confidence: 99%
“…Pregnancy is a good time to change oral hygiene and eating habits, so it is necessary to engage public and private dental offices in order to provide free dental services and the priority of admission to the dentist. If the language barrier is an obstacle to a dental visit, it is necessary to introduce linguistic mediators who will establish communication between dentists and pregnant women (Tušek et al, 2020), especially in multiethnic environments such as Vojvodina. It is necessary to redefine and consistently implement preventive programs, including education on oral health during prenatal care, pregnancy and puerperium.…”
Section: Resultsmentioning
confidence: 99%
“…For toddlers and preschool children, the ECC prevalence in our country varied and declined over time from 86% to 53% (studies conducted in the last 20 years, from southwest Herzegovina, northwest and east Bosnia and areas of Banja Luka, Mostar and Sarajevo) ( 20 - 24 ). In the neighboring countries, several studies showed further results in determining ECC prevalence: in Serbia results varied from 30.50-52.80% ( 25 , 26 ), in Croatia 56.50% ( 17 ), in Slovenia 56.50% ( 17 ), and in Kosovo 86.31% ( 27 ). The ECC prevalence in primary dentition of our study participants has reached pretty high values ( Table 2 ), and went over the most of recent local, regional, international and global findings, with reversive tendency to previous higher values.…”
Section: Discussionmentioning
confidence: 99%